Diseño del sistema de potencia y estructural de un parqueadero vertical rotatorio (2018)
This document presents the steps to follow in the process of designing a vertical parking and analyzes all its surroundings, since we started as an idea, the conceptual design and the detailed design of it. The foregoing in order to contribute to the search for solutions to a mobility problem in the main cities of Colombia. The most viable solution to the problem was raised, making use of the knowledge and computational tools available and bearing in mind that the solution was of low cost in its construction. The problem that was solved was identified and the necessary information was collected to establish the design requirements and restrictions. Then, the alternatives that have been sought were considered, the most convenient ones were cut, various criteria were taken into consideration, and with the alternatives selected, the design was finalized. In this degree work the design is divided into four parts, the storage design, the power transmission chain, the power transmission and the structural system, for the vertical carousel rotary parking lot. A detailed analysis was also carried out of all the elements that were related to the loads, to determine their dimensions and to know their mechanical behavior. At each step of the design process, SOLIDWORKS 3D modeler and ANSYS WORKBENCH were assisted as an engineering analysis program. These software’s helped and facilitated the detailed design process and they achieved it with the initial objectives set. Being a barn with a capacity of 16 cars, with overall dimensions of 4800 mm x 6400 mm x 17000 mm and with a maximum weight of 2200 Kg / vehicle